Central Bank Autonomy : Lessons from Global Trends - Laurens, Bernard (IMF Working Papers; Working Paper ;, 2007)
We calculate indexes of central bank autonomy (CBA) for 163 central banks as of end-2003, and comparable indexes for a subgroup of 68 central banks as of the end of the 1980s. The results confirm strong improvements in both economic and political CBA over the past couple of decades, although more progress is needed to boost political autonomy of the central banks in emerging market and developing countries. Our analysis confirms that greater CBA has on average helped to maintain low inflation levels. The paper identifies four broad principles of central bank autonomy that have been shared by the majority of countries. Significant differences exist in the area of banking supervision where many central banks have retained a key role. Finally, we discuss the sequencing of reforms to separate the conduct of monetary and fiscal policies.